The (Apparent) Absence of Women in the Praise of the Ancestors (Sir 44–49) - Pudełko, Jolanta Judyta (The Biblical Annals, 2016)
The Praise of the Ancestors (Sir 44–49) offers an interpretation of the story of Biblical Israel as seen through the eyes of Ben Sira. His telling of this story, permeated with God’s working, contains the names of male protagonists only. Still, analysis of textual versions of the Praise of the Ancestors (Hebrew, Greek and Syriac) enables us to detect some anonymous allusions to women (Sir 46:13; 47: 6.19; 48:19, 49:7). The present article attempts to investigate the reasons why there are no named references to Biblical heroines from Israel’s history, individuals who are mentioned in other books of the Bible. One answer might be found in the particular focus and educational purpose of the Praise, which was to provide a life model for young boys. Another reason might lie in the genre of the Praise, which was used in reference to women in Greek texts, but not in the Bible, where the name lists of praised heroes contained male names only. However, the most convincing reason for the absence of female names in the Praise of the Ancestors is found in its association with the priesthood of Biblical Israel. For the writer of the book, true high priests of the Jerusalem Temple constituted the ultimate keystone of the covenant between God and his people. Women, being absent from the official priesthood of Israel, are consequently absent from Sir 44–49.